2013
DOI: 10.1164/rccm.201302-0219oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Clearance Index as an Outcome Measure for Clinical Trials in Young Children with Cystic Fibrosis. A Pilot Study Using Inhaled Hypertonic Saline

Abstract: MBW testing is feasible in an interventional study in infants and preschool children with CF. These pilot findings support the development of MBW and LCI as an objective outcome measure in interventional trials in young children with CF, and provide estimates for sample size calculations for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 29 publications
3
106
0
5
Order By: Relevance
“…To date, one single-center study examined the usefulness of LCI (measured by respiratory mass spectrometry) in an interventional study in infants and preschool children (50). This add-on pilot study to the Infant Study of Inhaled Saline (ISIS) in CF trial (51) attempted MBW measurements in all 27 infant and preschool subjects participating in the Toronto center.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…To date, one single-center study examined the usefulness of LCI (measured by respiratory mass spectrometry) in an interventional study in infants and preschool children (50). This add-on pilot study to the Infant Study of Inhaled Saline (ISIS) in CF trial (51) attempted MBW measurements in all 27 infant and preschool subjects participating in the Toronto center.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…It is essential to have surrogate markers in order to define the disease severity status [3], to detect the lung destruction in earlier stages [4,5] or to estimate the effectiveness of a treating intervention [6][7][8][9][10][11][12]. An appropriate outcome measure has to meet some criteria: It must reflect the presence and severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…MBW is a non-invasive and safe test for assessing ventilation inhomogeneity. LCI is the most common index of uneven ventilation distribution and has recently been proposed as a sensitive marker for the detection of early pulmonary changes in CF [35][36][37] and the assessment of treatment effectiveness [6][7][8][9][10][11][12]. LCI seems to allow earlier detection of disease, compared to FEV 1 [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…As in previous years, the argument for bringing the CT scan and MBW forward as clinical end-points and relating these investigations to the various clinical outcomes is still hot topic [54]. In two studies, SHEIKH and co-workers [55,56] showed that HRCT during general anaesthesia and infant lung function testing (raised volume thoraco-abdominal compression technique) during sedation improved after intravenous antibiotic therapy in at total of 49 infants (21 in one study and 28 in the other) with CF at a mean age of 21 weeks, underscoring that untreated CF is a progressive disease.…”
Section: Cystic Fibrosismentioning
confidence: 99%